Implementation of Project-Based Learning Styles and Multiple Learning Objects to Promote the Pancasila Student Profile - Chotimah, Umi; Yanzi, Hermi; Sumarni, Sri; Syarifuddin, Syarifuddin; Ritonga, Joshua (Jurnal Pendidikan Progresif, 2023)
Implementation of Project-Based Learning Styles and Multiple Learning Objects to Promote  the Pancasila Student Profile. Objective: The objective of this study is to illustrate the implementation of project-based learning (PBL) based-on learning styles and multiple learning objects (MLO) to promote the Pancasila student profile. Methods: This quantitative study employs a descriptive research design involving 7th-grade students at SMPN 51 Palembang as the subjects. Data collection involves interviews, questionnaires, observations, and documentation. Descriptive statistical techniques are utilized for data analysis, while qualitative data is quantitatively analyzed. Findings: It was found that implementing learning in accordance with the PBL syntax using various learning media as MLO designed to match learning styles can stimulate the emergence of the six characters within the Pancasila student profile. Conclusion: The utilization of the PBL model aligned with learning styles and MLO can effectively foster the development of the Pancasila student profile. Keywords: project based learning, learning styles, multiple learning objectives, merdeka curriculum.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202332